Impulsive noise mitigation based adaptive filtering and Reed Solomon coding for power line communication - Asaad Jasim Mohammed; Maher Khudair Mahmoud Al-Azawi (Bulletin of Electrical Engineering and Informatics, 2023)
In the realm of power line communication (PLC), impulsive noise is often regarded as the most difficult challenge to face in PLC. The impulsive noise effects are reduced by employing a combined adaptive least mean square (LMS) filtering and Reed Solomon (RS) coding. As a result, the bit error rate (BER) and throughput performance over this channel are enhanced. The results of a MATLAB computer simulation indicated that a significant improvement is achieved by utilizing the LMS adaptive filter in conjunction with the RS code. This is in contrast to a system that utilizes RS code alone or a system that utilizes the conventional time domain clipping approach.